The application of positron emission tomography (PET/CT) in diagnosis of breast cancer. Part II. Diagnosis after treatment initiation, future perspectives - Jodłowska, Elżbieta; Czepczyński, Rafał; Czarnywojtek, Agata; Rewers, Amanda; Jarząbek, Grażyna; Kędzia, Witold; Ruchała, Marek (Contemporary Oncology/Współczesna Onkologia, 2016)
Similarly to the applications described in the first part of this publication, positron emission tomography with computed tomography (PET/CT) is also gaining importance in monitoring a tumour’s response to therapy and diagnosing breast cancer recurrences. This is additionally caused by the fact that many new techniques (dual-time point imaging, positron emission tomography with magnetic resonance PET/MR, PET/CT mammography) and radiotracers (16α-18F-fluoro-17β-estradiol, 18F-fluorothymidine) are under investigation. The highest sensitivity and specificity when monitoring response to treatment is achieved when the PET/CT scan is made after one or two chemotherapy courses. Response to anti-hormonal treatment can also be monitored, also when new radiotracers, such as FES, are used. When monitoring breast cancer recurrences during follow-up, PET/CT has higher sensitivity than conventional imaging modalities, making it possible to monitor the whole body simultaneously. New techniques and radiotracers enhance the sensitivity and specificity of PET and this is why, despite relatively high costs, it might become more widespread in monitoring response to treatment and breast cancer recurrences.